IMPLEMENTASI PENDIDIKAN LINTAS BUDAYA DALAM PROGRAM PERTUKARAN VIRTUAL TERHADAP PERSEPSI DAN PENGEMBANGAN TOLERANSI SISWA INTERNASIONAL - Mohammad Firmansyah; Dedi Gunawan Saputra; Jimmy Malintang; Thaharoh Ananda Mumtahana; Sonia Isna Suratin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In the era of globalization and digitalization, cross-cultural interactions are increasingly occurring through virtual spaces that connect individuals from various countries without geographical boundaries. This condition demands the presence of adaptive and inclusive intercultural education, one of which is through virtual exchange or Collaborative Online International Learning (COIL). Although previous research indicates that virtual exchange can improve intercultural competence, studies examining international students' perceptions of this experience and its contribution to the development of tolerance are still limited. Based on this gap, this study aims to analyze the implementation of cross-cultural education in virtual exchange programs, understand participants' perceptions of these experiences, and examine their contribution to the development of tolerance in the cognitive, affective, and behavioral domains. This study used a qualitative method with a literature review approach, through critical analysis of indexed journal articles, COIL program reports, and global education policy publications. Data were analyzed using content analysis techniques with source and theory triangulation based on the concepts of intercultural competence and experiential learning. The results show that virtual exchange has the potential to foster tolerance through cross-cultural collaborative learning. Pedagogical designs that emphasize critical reflection and collaborative tasks effectively develop cultural understanding, empathy, and cross-cultural cooperation. The novelty of this research lies in its identification of international students' perceptions as a key variable in mediating the formation of tolerance attitudes, as well as its integration of pedagogical analysis and empirical indicators of tolerance within a comprehensive theoretical framework.